Evaluation of nickel-cobalt deposition through the electrochemical impedance spectroscopy under magnetic field - Ebadi, M.; Mahmoudian, M.R.; Alias, Y.; Basirun, Wan Jefrey (E G Leuze Verlag, 2011)
Based on a dilute Watts bath, a nickel-cobalt electrolyte was formulated and its performance studied using Electrochemical Impedance Spectroscopy. The impedance spectrum is shown for electrodeposition at-0.9V and-I.IV in the presence of a permanent magnet field applied parallel to the cathode surface at a strength of 9T and in its absence. In the presence of such a magnetic field, a deposit with more uniform morphology was formed. Changes in deposit properties become less significant in the presence of AC, but even here, an effect is observed. Deposit properties were studied using SEM and AFM.